Life in High Salt Concentrations with Changing Environmental Conditions: Insights from Genomic and Phenotypic Analysis of Salinivibrio sp. - Jojy John (Microorganisms, 2019)
Life in salt pans with varying chemical compositions require special adaptation strategies at both the physiological and molecular level. The Marakkanam salt pan in South India is characterized with a high fluctuation in salinity (19−490 ppt), Ultravioletradiation, and heavy metal concentrations. Several bacterial species have been isolated and identified in the view of phylogenetic analysis and for the subsequent production of industrially important enzymes. However, limited information exists on the genomic basis of their survival under variable environmental conditions. To this extent, we sequenced the whole genome of the Salinivibrio sp. HTSP, a moderately halophilic bacterium. We analysed the physiological and genomic attributes of Salinivibrio sp. HTSP to elucidate the strategies of adaptation under various abiotic stresses. The genome size is estimated to be 3.39 Mbp with a mean G + C content of 50.6%, including 3150 coding sequences. The genome possessed osmotic stress-related coding sequences, and genes involved in different pathways of DNA repair mechanisms and genes related to the resistance to toxic metals were identified. The periplasmic stress response genes and genes of different oxidative stress mechanisms were also identified. The tolerance capacity of the bacterial isolates to heavy metals, UV-radiation, and salinity was also confirmed through appropriate laboratory experiments under controlled conditions.